The secret galaxy - Hodgkins, Fran, 1964- (Tilbury House, Publishers, 2014)
"When you gaze into the sky at night, what do you see? Most of us see only the brightest stars because they are the only ones that can cut through the artificial light that overwhelms the night. But up there, beyond the haze of streetlights and buildings, lies the Milky Way--our home galaxy. The words and photos in The Secret Galaxy allow young readers to see the stars as never before."--